EXPLORING IBUPROFEN: KEY ASPECTS OF PAIN RELIEF - A REVIEW OF ESTABLISHED SYNTHETIC METHODS (International Journal of Food and Nutritional Sciences, 2023)
Drug synthesis poses significant challenges for pharmaceutical chemists, who often seek multiple synthesis routes for the same drug candidate to minimize by-products and maximize yield. Low yield percentages in the synthetic process can lead to substantial losses in the industry. Ibuprofen, a widely used non-steroidal anti-inflammatory drug (NSAID), functions through non-selective inhibition of cyclooxygenase (COX) enzymes. Various synthetic routes for ibuprofen have been identified, with some being patented. These routes can be categorized as either conventional or green synthetic routes. The green synthesis of ibuprofen is particularly promising due to its higher yield and lower energy consumption compared to conventional methods. Notably, photochemical synthesis and BHC company's synthesis have significantly optimized yield percentage and atom efficiency. This review explores the various identified routes for ibuprofen synthesis, encompassing both conventional and green synthetic methods.